2018
DOI: 10.1097/meg.0000000000001204
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan versus proton-pump inhibitors for gastric endoscopic submucosal dissection-induced ulcers: a systematic review and meta-analysis

Abstract: Acid secretion inhibitors are usually prescribed to promote the healing of artificial ulcers caused by endoscopic submucosal dissection (ESD) to reduce the risk of gastric perforation and delayed bleeding. Vonoprazan is a newer agent that has been shown to be more potent than a proton-pump inhibitor (PPI). However, it remains unclear whether vonoprazan is more effective than PPI in promoting healing of ulcers caused by ESD. Medline and Embase databases were searched through January 2018 for studies that compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…However, there were still some differences between these meta‐analyses. One meta‐analysis included only 6 studies with a total of 461 patients, which is much less than those in the other meta‐analysis; and in the meta‐analysis by Kang et al, the healing rate at 8 weeks post‐ESD was significantly higher in the PPI group than in the vonoprazan group, which was contrary to that reported by Jaruvongvanich et al's study . These results are different from our study because two studies were not included in their studies.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…However, there were still some differences between these meta‐analyses. One meta‐analysis included only 6 studies with a total of 461 patients, which is much less than those in the other meta‐analysis; and in the meta‐analysis by Kang et al, the healing rate at 8 weeks post‐ESD was significantly higher in the PPI group than in the vonoprazan group, which was contrary to that reported by Jaruvongvanich et al's study . These results are different from our study because two studies were not included in their studies.…”
Section: Discussioncontrasting
confidence: 89%
“…Recently, there have been two meta‐analyses focusing on the efficacy and safety of vonoprazan compared with PPIs for treating post‐ESD ulcers, both showing that vonoprazan treated artificial ulcers more rapidly and effectively than PPIs. However, there were still some differences between these meta‐analyses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] However, Otsuka et al reported that most ESD-induced ulcers were actually healed by 4 weeks, which implies that early-phase (by 2 weeks) evaluation is important for effective drug treatment. The previous meta-analyses [ 30 32 ] did not assess 2-week evaluation points and featured biased study selection and data extraction. Furthermore, several additional clinical trials [ 18 , 20 , 25 ] were published after these meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Although several reports have supported the conclusion that vonoprazan promotes more effective postoperative healing [33][34][35], some found no difference in its ulcer-healing ability, 4 or 8 weeks following gastric ESD [36,37]. A systematic review and meta-analysis of these reports showed that patients treated with vonoprazan demonstrated a significantly higher rate of completely healed ulcers, compared to that observed in those managed with PPIs [38]. Although controversy remains regarding the ▶ Table 3 Incidence rate of post-endoscopic submucosal dissection (ESD) bleeding.…”
Section: Discussionmentioning
confidence: 99%